The pattern of criminal behavior in psychopaths and neurologists - doudou, sonia (Journal of Social Sciences and Humanities, 2020)
This study aimed to identify the pattern of criminal behavior of psychopath and neurologists at France-Fanon Hospital in Balida. The importance of our study can be limited to the fact a very sensitive subject criminal behavior as well as variable psychopathic personality and neurotic character, because these disorders are at the root of most problems that waste the human energy and are subject to society. The study sample included 40 people, including 22 psychopaths and 18 neurologists. In accordance with the nature of the current study, the researcher has adopted a comparative descriptive approach, which makes it possible to describe the phenomenon studied and quantified by the collection of codified information on the problem and their classification and subject to a thorough study applied the measure of criminal behavior prepared by the researcher The results of the study indicate that the criminal behavior of psychopaths is true, but that the degree obtained by the individual corresponds to the degree of criminal behavior, which is not less than 94 degrees. He also pointed out that the type of criminal behavior in neurons is not true on a scale of behavior obtained by the individual in the criminal behavior type scale, which is less than 94 degrees, that is, to say that if the threshold is below this threshold, the type of criminal behavior in the individual is not real.